Technical Note: Calibrating radiochromic film in beams of uncertain quality. Issue 10 (23rd September 2016) - Peet, Samuel C.; Wilks, Rachael; Kairn, Tanya; Trapp, Jamie V.; Crowe, Scott B.
Abstract : Purpose: The dose‐response of radiochromic film has been shown to be dependent on the quality of the incident radiation, particularly at low energies. Difficulty therefore arises when a calibration is required for radiation of uncertain energy. This study investigates the ability of a recently published calibration method [see M. Tamponi et al., "A new form of the calibration curve in radiochromic dosimetry. Properties and results, " Med. Phys.43, 4435–4446 (2016)] to reduce the energy‐dependence of radiochromic film. This allows for corrections to be applied that may improve the accuracy and precision of measurements taken in beams of uncertain energy or where the beam quality is known but calibration doses cannot be delivered. Methods: Gafchromic EBT3 film was irradiated with a range of superficial, orthovoltage, and high‐energy photon beams. Calibrations were then applied using a typical net optical density approach and compared with the Tamponi et al. method that instead defines the response as a ratio of two net optical densities. To quantify the energy dependence, the response at each beam quality and dose was then normalized to the response at a preselected reference quality. This resulted in a relative measure that could be used to correct the calibration curve at the reference beam quality to any other quality of interest. Results: The Tamponi et al. calibration method resulted in substantially less energy dependence compared to the standard net optical density approach, without compromising the calibration fit. The maximum deviation from the reference beam calibration curve was 7% across the range of energies and doses analyzed, reducing to <3% for doses greater than 200 cGy. However, the ability of the calibration curve to fit the data deteriorated as the curve was refitted with measurements at higher doses than those originally studied. Conclusions: The Tamponi et al. calibration method, based on the ratio of two net optical densities, considerably reduces the energy dependence of Gafchromic EBT3 film. Manipulating the calibration data in the fashion presented in this study allows for a readily available calibration curve to be corrected to represent calibration curves at different energies. This may be useful when a calibration is desired for a beam where the delivery of a set of calibration doses is problematic, such as with out‐of‐field measurements, radioactive sources, and imaging applications.